Experience of voluntary support provision in youth is associated with later‐life supportive actions: A community‐based study in Japan. (18th October 2022) - Takase, Mai; Murayama, Hiroshi
Abstract: Enhancing the voluntary supportive actions of older adults towards other community‐dwelling citizens is an important measure for a healthy community. Volunteering action in adulthood is related to the volunteering actions of older adults' parents, which they remember from their youth. In this study, the association between parents' former voluntary supportive actions and the current voluntary supportive actions of older adults is explored. Questionnaires were distributed to community‐dwelling citizens aged 65 years and above, in Tokamachi city, Niigata Prefecture, Japan (response rate: 81.7%). Participants self‐reported their current voluntary supportive actions and reported on their parents' former voluntary actions during their youth. The results indicated that the current voluntary supportive actions of the study participants were related to the former voluntary actions of their parents (OR: 2.28, 95% CI: 1.62–3.20). Moreover, the participants were more likely to extend support in contexts which are more closely related to one's private life, only when their parents provided support in those private contexts. The study provides implications for the importance of considering life experiences when facilitating voluntary supportive actions and renders information on how unique strategies should to be implemented to involve individuals who are unfamiliar with volunteering actions.